Indoor air quality in elderly homes in Serbia - Evidence-based design methodology - Vujovic, Milica; Komatina, Mirko; Manic, Dimitrije; Milos, Marko (Industrija, 2022)
This study represents the first phase of research into the relationship between indoor air quality and the architectural and mechanical characteristics of buildings. The focus is on specific categories of users such as the elderly. The research methodology based on the scientific method is presented, which examines the condition of real objects on the territory of the Republic of Serbia. The aim is to provide a sound methodology for establishing the link between architecture, mechanical systems and indoor air quality, on evidence-based design principles, in order to propose guidelines for future interventions in the construction or adaptation of facilities for the elderly. Second objective of the study is to point to the relevance of contextualizing interventions according to the user groups that are targeted and reinforce application of scientific evidence in contemporary building design. Namely, tailor-made solutions would be necessary in the future, and consideration towards different user needs should be framed and structured in order to meaningfully operationalize the design.